2014
DOI: 10.4103/2229-516x.125678
|View full text |Cite
|
Sign up to set email alerts
|

Altered biliary flow rate and bile composition following consumption of ethanolic fruit extract of Dennettia in rats

Abstract: Background:Dennettia tripetala is a tropical plant with some ethno-medicinal uses; it enhances uterine contraction/involution in pregnant and post-partum women, it is also a mild laxative, with anti-bacteria, antifungal properties etc.,Aims:This study sought to elucidate the impact of D. tripetala fruit extract intake on biliary flow rate and bile composition in rats.Materials and Methods:A total of 18 albino Wistar rats were randomly assigned into three groups of 6 rats each and fed on normal rat chow + drink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…A number of studies have been carried out to ascertain the toxicity of DT. Although DT has been reported to contain uvariopsin, an alkaloid which improves bile secretion and attenuates hepatic disorders [ 22 , 23 ], a study by Ofem and colleagues [ 22 ] showed that the ethanolic extract of DT fruits administered at a certain dose reduces bile production in normal healthy rats. The extract also caused an increase in sodium, potassium, and bicarbonate ions in bile and reduced the chloride and unconjugated bilirubin content of bile [ 22 ].…”
Section: Research On Dennettia Tripetalamentioning
confidence: 99%
“…A number of studies have been carried out to ascertain the toxicity of DT. Although DT has been reported to contain uvariopsin, an alkaloid which improves bile secretion and attenuates hepatic disorders [ 22 , 23 ], a study by Ofem and colleagues [ 22 ] showed that the ethanolic extract of DT fruits administered at a certain dose reduces bile production in normal healthy rats. The extract also caused an increase in sodium, potassium, and bicarbonate ions in bile and reduced the chloride and unconjugated bilirubin content of bile [ 22 ].…”
Section: Research On Dennettia Tripetalamentioning
confidence: 99%
“…Reactive oxygen species (ROS) are usually generated as part of metabolism in living organism and the effects of these species are prevented by antioxidants. Some of these antioxidants are endogenous that is produced in the body, while others are obtained from plants in the form of antioxidant nutrients (26). Several studies have shown that D. tripetalais used in the management of oxidative stress related diseases and infections (27).…”
Section: Effect On Oxidative Stress and Antioxidant Activitiesmentioning
confidence: 99%
“…A number of studies have been carried out to investigate the toxic effect of D. tripetala. D. tripetala has been shown to contain uvariopsin, an alkaloid that helps to improves bile secretion and reduces hepatic disorders (26,40). However, a study by Ofemet al, (26) discovered that the ethanolic extract of D. tripetala fruits given at a certain dose reduces bile production in normal healthy rats.…”
Section: Toxicity Of Dennettia Tripetalamentioning
confidence: 99%
“…Most of the major transporters and enzymes that determine the mechanisms of bile formation and secretion in hepatocytes have been characterized at the molecular level, offering the opportunity to regulate this process therapeutically . Phytochemicals in some herb or plant food have been reported to increase bile secretion through the synthesis of bile salts, changes in transporter expression/activity and the evocation of signalling pathways . A diet rich in phospholipids can also increase bile formation and bile acid transport .…”
Section: Possible Interventions To Increase the Elimination Of Popsmentioning
confidence: 99%